Lactobacillus plantarum CCFM8610 Alleviates Irritable Bowel Syndrome and Prevents Gut Microbiota Dysbiosis: A Randomized, Double-Blind, Placebo-Controlled, Pilot Clinical Trial. (March 2021) - Liu, Yang; Yu, Xinjie; Yu, Leilei; Tian, Fengwei; Zhao, Jianxin; Zhang, Hao; Qian, Long; Wang, Qun; Xue, Zhengqing; Zhai, Qixiao; Chen, Wei
Highlights: L. plantarum CCFM8610 alleviated clinical symptoms of IBS-D. L. plantarum CCFM8610 improved the quality of life of IBS-D patients. L. plantarum CCFM8610 recovered gut microbiota dysbiosis. Beneficial effects may be due to the increase of butyric acid–producing bacteria. Abstract: Irritable bowel syndrome with diarrhea (IBS-D) is chronic intestinal dysfunction with diarrhea and other complicated clinical symptoms, and it has a great impact on the daily life and mental state of patients. Some studies have reported that ingestion of probiotics can significantly alleviate a variety of intestinal diseases. The purpose of this study was to investigate the IBS-D-alleviating effects of a probiotic strain, Lactobacillus plantarum (L. plantarum) CCFM8610, with multiple health-promoting effects. The study was a 12-week, randomized, double-blind, placebo-controlled, pilot clinical trial. Seventy-five patients were randomly assigned to receive the placebo, oligosaccharides, or L. plantarum CCFM8610 (1 × 10 10 colony-forming units (CFU) per day), with a 2-week run-in period, an 8-week intervention period, and a 2-week follow-up observation period. The patients' clinical symptoms and quality of life were examined by the IBS symptom severity scale (IBS-SSS) and the IBS quality of life scale (IBS-QOL). Changes in gut microbiota composition and diversity were measured at the end of the intervention period. The oral administration of L. plantarum CCFM8610 significantly decreased the IBS-SSS and IBS-QOL scores, reduced IBS-D symptom severity, recovered gut microbiota diversity, decreased the relative abundance of bloating-related genus Methanobrevibacter, and increased the relative abundance of butyric acid-producing genera, including Anaerostipes, Anaerotruncus, Bifidobacterium, Butyricimonas, and Odoribacter . These findings suggest that ingestion of L. plantarum CCFM8610 can significantly alleviate clinical symptoms and gut microbiota dysbiosis in IBS-D patients. The IBS-D-alleviating effect of L. plantarum CCFM8610 may be related to the increase in the relative abundance of butyric acid-producing genera in the intestine.